The Polymorphisms of the Peroxisome-Proliferator Activated Receptors' Alfa Gene Modify the Aerobic Training Induced Changes of Cholesterol and Glucose - Maciejewska-Skrendo, Agnieszka; Buryta, Maciej; Czarny, Wojciech; Król, Pawel; Stastny, Petr; Petr, Miroslav; Safranow, Krzysztof; Sawczuk, Marek (Journal of clinical medicine, 2019)
BACKGROUND: PPARα is a transcriptional factor that controls the expression of genes involved in fatty acid metabolism, including fatty acid transport, uptake by the cells, intracellular binding, and activation, as well as catabolism (particularly mitochondrial fatty acid oxidation) or storage. PPARA gene polymorphisms may be crucial for maintaining lipid homeostasis and in this way, being responsible for developing specific training-induced physiological reactions. Therefore, we have decided to check if post-training changes of body mass measurements as well as chosen biochemical parameters are modulation by the PPARA genotypes. METHODS: We have examined the genotype and alleles' frequencies (described in PPARA rs1800206 and rs4253778 polymorphic sites) in 168 female participants engaged in a 12-week training program. Body composition and biochemical parameters were measured before and after the completion of a whole training program. RESULTS: Statistical analyses revealed that PPARA intron 7 rs4253778 CC genotype modulate training response by increasing low-density lipoproteins (LDL) and glucose concentration, while PPARA Leu162Val rs1800206 CG genotype polymorphism interacts in a decrease in high-density lipoproteins (HDL) concentration. CONCLUSIONS: Carriers of PPARA intron 7 rs4253778 CC genotype and Leu162Val rs1800206 CG genotype might have potential negative training-induced cholesterol and glucose changes after aerobic exercise.
Keywords: genetic predisposition; glucose tolerance; human performance; cholesterol levels; aerobic training; mitochondria activity; lipid metabolism; VO2max